2021
DOI: 10.1021/acsaelm.1c00671
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Intrinsic Nature of Organic Semiconductors Using a Metal Contact-Induced Capacitance Study in Organic Metal–Insulator–Semiconductor Capacitors

Abstract: Whether organic semiconductors, in their pristine form, are inherently intrinsic or involuntarily doped is an open question that is yet to be addressed. In this work, the source of charge carriers within pristine organic semiconductors, processed in a controlled inert ambience, is investigated using organic metal− insulator−metal capacitor (OMISCAP) devices. Top-gate and bottom-gate architecture of OMISCAP devices based on various organic semiconductors along with different combinations of metal−semiconductor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The organic-metal-insulator-semiconductor capacitor (OMISCAP) has been considered to be an indispensable device structure to predict the performance of organic thin film transistors (OTFTs) [1][2][3][4][5][6][7]. Thorough investigations of the OMISCAP operation on the basis of the charge injection through the thermionic emission at the metal-semiconductor junction and the charge distribution under the influence of gate electric field have been reported recently [8][9][10][11][12]. The capacitance-voltage (C − V) characteristics of OMISCAP * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The organic-metal-insulator-semiconductor capacitor (OMISCAP) has been considered to be an indispensable device structure to predict the performance of organic thin film transistors (OTFTs) [1][2][3][4][5][6][7]. Thorough investigations of the OMISCAP operation on the basis of the charge injection through the thermionic emission at the metal-semiconductor junction and the charge distribution under the influence of gate electric field have been reported recently [8][9][10][11][12]. The capacitance-voltage (C − V) characteristics of OMISCAP * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…However, using this model results in significant deviations from experimental data. Gupta et al have demonstrated that thickness does have an intrinsic effect on current output through increasing charge mobility away from the dielectric interface and bulk donor traps contributing to a complex thickness -current relationship [462], [463].…”
Section: Electronic Testingmentioning
confidence: 99%